Performance measurement system mechanisms and service process type - Mohd Amir, Amizawati; Nik Ahmad, Nik Nazli; Mohamad, Muslim Har Sani (Faculty of Economics and Business, Universiti Kebangsaan Malaysia, 2010)
The paper adds to the stream of Performance Measurement System (PMS) research with understanding the relationship between service activities and PMS design. Focusing on the association between service process types and the ways of measuring activities, the study provides a preliminary exploratory study on the practical aspect of PMS design. Using a combination of both survey and in depth interviews, the findings show that service type has insignificant relationship with choice of measurement mechanisms. Instead other factors, strategy, intensity of competition and size, determine the measurement approaches. More importantly, the results indicate that the PMS mechanisms of professional service firms are not much different from that of mass service firms. The evidence, thus, suggests that PMS is designed in a way that matches the organizational objectives rather than focuses on the uniqueness of service businesses